Innovating Sustainable Supply Chains in Information Technology Industry - Tathavadekar, Viraj (Digital Repository of Theses, 2026)
This study looks at how to make the supply chains of the Information Technology (IT) industry more environmentally friendly, with a focus on how digital transformation and including stakeholders may help. As global supply chains get more complicated and harmful to the environment, IT firms are under more and more pressure to use sustainable supply chain management (SSCM) techniques that find a balance between making money and being responsible for the environment and society. The study looks into how technologies like AI, blockchain, and the IoT may make IT supply networks more open, efficient, and ethical. The study also looks at how circular economy models, corporate social responsibility, and national and international laws affect sustainability efforts. We used a mixed-methods approach, which included both qualitative interviews and quantitative analysis with SPSS and MS Excel. The data was looked at using methods like mean, standard deviation, regression, and correlation. The results show that big IT companies are making good progress, but small and medium-sized businesses (SMEs) are still having trouble since they don't have the resources and the rules aren't always clear. The study ends with a proposed framework that shows the drivers, impediments, and strategic enablers that the IT sector needs to create sustainable supply chains. Keywords : Sustainable Supply Chain Management (SSCM), Information Technology Industry, Artificial Intelligence (AI), Blockchain, Circular Economy, Corporate Social Responsibility (CSR), SPSS, Stakeholder Engagement.